2019
DOI: 10.1088/1361-651x/ab2de0
|View full text |Cite
|
Sign up to set email alerts
|

Basal dislocation/precipitate interactions in Mg–Al alloys: an atomistic investigation

Abstract: The interaction between edge basal dislocations and β-Mg 17 Al 12 precipitates was studied using atomistic simulations. A strategy was developed to insert a lozenge-shaped Mg 17 Al 12 precipitate with Burgers orientation relationship within the Mg matrix in an atomistic model ensuring that the matrix/precipitate interfaces were close to minimum energy configurations. It was found that the dislocation bypassed the precipitate by the formation of an Orowan loop, that entered the precipitate. Within the precipita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 75 publications
(130 reference statements)
4
14
0
Order By: Relevance
“…Mg-RE alloy showed that basal dislocations have to pile-up at precipitate/matrix interface before they were able to shear the precipitate. These results are in agreement with recent molecular dynamics simulations by Esteban-Manzanares et al [47] which showed that the first dislocation entered the precipitate but was not able to progress further, leading to the formation in Mg and they rapidly form loops around the precipitates. Experimental evidence [48] showed that sometimes the dislocations were attracted by the precipitate/matrix interface and preferred to glide along the interface rather than shear the precipitate and similar observations were provided by molecular dynamics simulations [47].…”
Section: Interaction Mechanisms Of Basal Dislocations With # Precipitsupporting
confidence: 93%
See 2 more Smart Citations
“…Mg-RE alloy showed that basal dislocations have to pile-up at precipitate/matrix interface before they were able to shear the precipitate. These results are in agreement with recent molecular dynamics simulations by Esteban-Manzanares et al [47] which showed that the first dislocation entered the precipitate but was not able to progress further, leading to the formation in Mg and they rapidly form loops around the precipitates. Experimental evidence [48] showed that sometimes the dislocations were attracted by the precipitate/matrix interface and preferred to glide along the interface rather than shear the precipitate and similar observations were provided by molecular dynamics simulations [47].…”
Section: Interaction Mechanisms Of Basal Dislocations With # Precipitsupporting
confidence: 93%
“…These results are in agreement with recent molecular dynamics simulations by Esteban-Manzanares et al [47] which showed that the first dislocation entered the precipitate but was not able to progress further, leading to the formation in Mg and they rapidly form loops around the precipitates. Experimental evidence [48] showed that sometimes the dislocations were attracted by the precipitate/matrix interface and preferred to glide along the interface rather than shear the precipitate and similar observations were provided by molecular dynamics simulations [47]. It should be noticed that first principles calculations of the generalized stacking fault energy have shown that high shear stresses are necessary to promote dislocation slip in these intermetallic phases [49] and, thus, several dislocations have to pile-up before the Orowan loop can penetrate and collapse within the precipitate.…”
Section: Interaction Mechanisms Of Basal Dislocations With # Precipitsupporting
confidence: 93%
See 1 more Smart Citation
“…14,[18][19][20][21] Prominent examples can be found in aluminium alloys that play increasingly crucial roles in various industrial products. 5,[8][9][10][11][12][22][23][24][25] One of the main goals of alloying matrices is to obtain the most lightweight and high-strength alloys that can be extensively used in aircraft industries, modern trains and vehicles, and so forth. The central mechanisms for enhancing the strength of aluminium is to produce uniform distributions of nucleated precipitates and solid microstructures in the aluminium matrix with different solute elements such as Zn, Mg, Si, Cu, Mn, and Cr.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the details of the dislocation/precipitate interaction in these alloys as well as the strengthening provided are not well known. Consequently, MS and MD were carried out to assess the interaction between basal dislocations and β-Mg 17 Al 12 precipitates in Mg-Al alloys (Esteban-Manzanares et al, 2019b). Dickel et al (2018), which stand for 2NN-MEAM potentials.…”
Section: Dislocation/precipitate Interaction In Mg-almentioning
confidence: 99%